THE IMPORTANCE OF A CAPITAL ADEQUACY FOR ISLAMIC BANKS - Ghandour, Ghassan Farouk (International Journal of Research -GRANTHAALAYAH, 2017)
Conceptually, an Islamic bank has an equity-based capital structure, dominated by shareholders’ equity and investment deposits based on profit and loss sharing [PLS]. There is no need for capital adequacy regulations if the Islamic banks are structured as pure PLS-based organizations. However, due to informational asymmetry and risk aversion by investors, there currently exist fixed claim liabilities on the Islamic banking balance sheets. This necessitates the imposition of capital adequacy requirements, which aim at maintaining systemic stability by achieving two fundamental objectives. First, capital regulations should protect risk-averse (assumed unsophisticated) depositors. This requires a minimum equity capital cushion and an optimal assets-liabilities composition. Second, capital regulations should give the right incentives to shareholders to promote prudent behavior by the banks. This requires analysis of the effect of financial participation by shareholders on Pareto optimality, and analysis of potential behavior by shareholders when facing financial uncertainty.